Application of Material Flow Cost Accounting Technique in Process of Warehouse Management for XYZ Company - Jantrathip, Monthip; Mokkhamakkul, Tartat; Wongkaew, Wila-Sini (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research is to apply Material Flow Cost Accounting with warehouse management in XYZ company by selecting a fast-moving product for the analysis, including Super premium product, Premium product, Standard product, and Economy product. Cost data related to each step were collected for analyzing losses according to Material Flow Cost Accounting technique. The study revealed that the greatest portion of negative product cost resulted from material cost, followed by system cost and energy cost. It was also found that negative product cost of Super premium product, Premium product, Standard product, and Economy product was 0.044%, 0.062%, 0.089% and 0.158% respectively. The total daily cost of losses of 4 products was 1,676.88 baht which was incurred in the process of preparation.